2022
DOI: 10.3389/fpubh.2022.859132
|View full text |Cite
|
Sign up to set email alerts
|

Association of sociodemographic and lifestyle factors with dietary patterns among men and women living in Mexico City: A cross-sectional study

Abstract: BackgroundDiet is one of the leading risk factors for non-communicable diseases and is related to sociodemographic and lifestyle factors, including sex. These associations vary across populations. We aimed to investigate which factors are associated with dietary patterns among adults living in Mexico City by sex.MethodsWe used data from the Mexico City Diabetes Representative Study, a cross-sectional, multistage, stratified, and cluster-sampled survey in Mexico City (n = 1,142; 413 men and 729 women). Dietary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
4
3
0
1
Order By: Relevance
“…The main difference between the study populations was the presence of a dietary pattern composed exclusively of foods with some degree of processing, "Processed", which represented the highest percentage of variation in the diet of the Pernambuco population (16.5%). Similar findings to this study have been reported in other Latin American populations, such as Mexico, 40 Argentina 41 and Chile. 42 Brazil and Colombia are inserted in a hegemonic global food system, where the guidelines of world food trade cross the diet of the population, and the supply of food is limited to particular varieties and species, which has led to a "homogenisation" in food patterns 43 ; in the present study, it was found that the food patterns identificated in both populations are composed of similar food groups, which confirms this trend to homogenisation and responds to one of initial study hypotheses.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The main difference between the study populations was the presence of a dietary pattern composed exclusively of foods with some degree of processing, "Processed", which represented the highest percentage of variation in the diet of the Pernambuco population (16.5%). Similar findings to this study have been reported in other Latin American populations, such as Mexico, 40 Argentina 41 and Chile. 42 Brazil and Colombia are inserted in a hegemonic global food system, where the guidelines of world food trade cross the diet of the population, and the supply of food is limited to particular varieties and species, which has led to a "homogenisation" in food patterns 43 ; in the present study, it was found that the food patterns identificated in both populations are composed of similar food groups, which confirms this trend to homogenisation and responds to one of initial study hypotheses.…”
Section: Discussionsupporting
confidence: 92%
“…The main difference between the study populations was the presence of a dietary pattern composed exclusively of foods with some degree of processing, “Processed”, which represented the highest percentage of variation in the diet of the Pernambuco population (16.5%). Similar findings to this study have been reported in other Latin American populations, such as Mexico, 40 Argentina 41 and Chile 42 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, female participants exhibited a higher level of knowledge than male participants, confirming sex-related differences in knowledge of fruits and vegetables [ 41 , 61 ]. Women are often associated with concerns about their appearance and tend to adopt a more health-conscious approach to eating [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%